The activity demands and physiological responses encountered during basketball match-play: A systematic review - Johnston, K.; Wattie, N.; Schorer, J.; Baker, J. (Sports Medicine, 2018)
Background: Basketball is a popular, court-based team sport that has been extensively studied over the last decade. Objective: The purpose of this article was to provide a systematic review regarding the activity demands and physiological responses experienced during basketball match-play according to playing period, playing position, playing level, geographical location, and sex. Methods: An electronic database search of relevant articles published prior to 30 September 2016 was performed with PubMed, MEDLINE, ERIC, Google Scholar, SCIndex, and ScienceDirect. Studies that measured activity demands and/or physiological responses during basketball match-play were included. Results: Following screening, 25 articles remained for review. During live playing time across 40-min matches, male and female basketball players travel 5-6 km at average physiological intensities above lactate threshold and 85% of maximal heart rate (HR). Temporal comparisons show a reduction in vigorous activities in the fourth quarter, likely contributing to lower blood lactate concentrations and HR responses evident towards the end of matches. Guards tend to perform a higher percentage of live playing time sprinting and performing high-intensity shuffling compared with forwards and centers. Guards also perform less standing and walking during match-play compared with forwards and centers. Variations in activity demands likely account for the higher blood lactate concentrations and HR responses observed for guards compared with forwards and centers. Furthermore, higher-level players perform a greater intermittent workload than lower-level players. Moreover, geographical differences may exist in the activity demands (distance and frequency) and physiological responses between Australian, African, and European basketball players, whereby Australian players sustain greater workloads. While activity demands and physiological data vary across playing positions, playing levels, and geographical locations, male and female players competing at the same level experience similar demands. Conclusion: The current results provide a detailed description of the specific requirements placed on basketball players during match-play according to playing period, playing level, playing position, geographical location, and sex, which may be useful in the development of individualized basketball training drills.